Humanistic Islamic Leadership: A Thematic Hadith Study on the Prohibition of Tyranny in Political and State Governance Contexts - Devita Maharani, Nadia; Maftuh Ajmain; Muhammad Alif; Hikmatul Luthfi (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2025)
This study examines the virtue of knowledge (fadl al-‘ilm) in Islam through a comparative analysis of two major Hadith compilations: Jami’ at-Tirmidhi by Imam at-Tirmidhi and Riyadhus Shalihin by Imam an-Nawawi. In Islamic teachings, knowledge occupies a central position in shaping character, building civilization, and serving as a spiritual means of drawing closer to Allah ﷻ. The first revelation commanding humankind to “read” underscores the fundamental importance of knowledge in Islam. Both Hadith collections selected for this research present narrations on the excellence of knowledge with distinct approaches and structures, making them particularly interesting to explore thematically.This study employs a qualitative methodology using a library research approach and thematic (maudhu’i) analysis. The research procedures include identifying Hadiths related to knowledge, classifying them into subthemes, conducting a comparative analysis of their wording, meaning, and context, and drawing conclusions on the similarities and differences in their presentation. The findings are expected to enrich the understanding of the methodological characteristics of both works in addressing the theme of knowledge, as well as to contribute to the development of thematic Hadith studies and Islamic thought in general.